2023
DOI: 10.3390/foods12224178
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Roasting Methods on the Phenolic Contents, Antioxidant Potential, and In Vitro Inhibitory Activities of Sacha Inchi Seeds

Suwapat Kittibunchakul,
Varongsiri Kemsawasd,
Chatrapa Hudthagosol
et al.

Abstract: Roasted sacha inchi seeds are now commercialized as a health food product, but the influence of roasting methods on their proclaimed health effects has yet to be explored. This study investigated the total phenolic contents (TPCs), antioxidant potential, and inhibitory activities of raw and roasted sacha inchi seeds in vitro. Individual phenolics in raw seeds were also identified in an attempt to explain the bioactivities of the seeds. The results suggested that roasting in a cooking pan, vacuum oven, and tray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…FRAP values exhibited a significant increase (p < 0.05) during soaking for 2 and 12 h and roasting for 5 and 6 min, then gradually decreased after soaking for 24 h and roasting for 7 min. A similar result was observed by Kittibunchakul et al [49], who found a significant increase in the FRAP after roasting of sacha inchi seeds. The generation of Maillard reaction products upon roasting, which contribute to antioxidant properties, may be the cause of the increase in FRAP levels [46].…”
Section: Change In Antioxidant Activitysupporting
confidence: 89%
“…FRAP values exhibited a significant increase (p < 0.05) during soaking for 2 and 12 h and roasting for 5 and 6 min, then gradually decreased after soaking for 24 h and roasting for 7 min. A similar result was observed by Kittibunchakul et al [49], who found a significant increase in the FRAP after roasting of sacha inchi seeds. The generation of Maillard reaction products upon roasting, which contribute to antioxidant properties, may be the cause of the increase in FRAP levels [46].…”
Section: Change In Antioxidant Activitysupporting
confidence: 89%